2019
DOI: 10.1136/tsaco-2019-000340
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative REBOA: an analysis of the American Association for the Surgery of Trauma AORTA registry

Abstract: BackgroundResuscitative endovascular balloon occlusion of the aorta (REBOA) is a less-invasive technique for aortic occlusion (AO). Commonly performed in the emergency department (ED), the role of intraoperative placement is less defined. We hypothesized that operating room (OR) placement is associated with increased in-hospital mortality.MethodsThe American Association for the Surgery of Trauma AORTA registry was used to identify patients undergoing REBOA. Injury characteristics and outcomes data were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
1
17
0
3
Order By: Relevance
“…Furthermore, many variables can affect survival in this category of patients: pre-hospital time, prompt recognition of bleeding site(s), availability of expert surgeon, time to operating room, appropriate transfusion protocol, physiology of the patient. Time to operating room and physiologic state of patients may predict outcome as importantly as does whether a REBOA is used [ 41 ]. Due to these considerations, further investigations with an adequate volume of cases considering all possible confounders can help to understand the efficacy of REBOA in torso haemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many variables can affect survival in this category of patients: pre-hospital time, prompt recognition of bleeding site(s), availability of expert surgeon, time to operating room, appropriate transfusion protocol, physiology of the patient. Time to operating room and physiologic state of patients may predict outcome as importantly as does whether a REBOA is used [ 41 ]. Due to these considerations, further investigations with an adequate volume of cases considering all possible confounders can help to understand the efficacy of REBOA in torso haemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“… 16 17 The rate of AKI in REBOA, specifically, has been previously reported to be 19% in a cohort with an in-hospital mortality rate of 63%. 18 Although the rate of AKI in the subjects of our study is much higher, the total mortality rate is much lower (49.1%). We find it paramount to note that complications such as AKI and MOF can only develop in a patient that is alive and in the ICU.…”
Section: Discussionmentioning
confidence: 48%
“…First, individual trauma surgeons have varied practices with regards to the management of the hypotensive trauma patient, and surgeons with prior REBOA experience may be more likely to choose this intervention. Two patients had REBOA placed despite not meeting algorithm indications as they were never hypotensive; however, these were placed due to intraoperative hemorrhage and previous research has found that intraoperative REBOA placements are more likely to occur in patients with stable initial hemodynamics [17]. Two patients had REBOA placed despite widened mediastinum on CXR.…”
Section: Discussionmentioning
confidence: 92%